Application of Demonstration Method in Improving Beginning Writing Skills in Grade I Students Elementary School - Yusmiyanti, Yusmiyanti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to describe the application of the demonstration method in improving the skills and learning outcomes of early writing skill for grade 1 elementary school students. The demonstration method provides a learning experience so students can master the lesson or understand the concept well and correctly through the process of observing and imitating what the teacher has demonstrated directly or through relevant image media. The research method used is classroom action research. Data collection techniques are tests, observations and interviews. The data obtained was analyzed using comparative description analysis. This Classroom Action Research was carried out in 2 cycles with procedures in each cycle starting from planning, implementation, observation and reflection.The results of the study showed that basic competency in early writing skill of perpendicular letters increased the average value of student learning outcomes by 1.3 from pre-cycle to cycle 1 and 6.2 from cycle 1 to cycle 2, students who obtained learning outcome scores above the KKM ( 60) also increased from 60% in the pre-cycle to 90% in cycle 1 and 100% in cycle 2.